Metastatic stage vs complications at radical nephrectomy with inferior vena cava thrombectomy. (June 2022) - Hoeh, Benedikt; Flammia, Rocco Simone; Hohenhorst, Lukas; Sorce, Gabriele; Panunzio, Andrea; Chierigo, Francesco; Nimer, Nancy; Tian, Zhe; Saad, Fred; Gallucci, Michele; Briganti, Alberto; Shariat, Shahrokh F.; et al.
Abstract: Background: To investigate perioperative complication rates at radical nephrectomy (RN) according to inferior vena cava thrombectomy (IVC-T) status and stage (metastatic vs non-metastatic) within kidney cancer patients. Materials and methods: We ascertained perioperative complication rates within the National Inpatient Sample database (2016–2019). First, log-link linear Generalized Estimating Equation function (GEE) regression models (adjusted for hospital clustering and weighted for discharge disposition) tested complication rates in IVC-T patients, according to metastatic stage. Subsequently, a subgroup analysis relied on RN patients with or without IVC-T. Here, multivariable logistic regression models tested complication rates in RN patients according to IVC-T status, after propensity score matching including metastatic stage. Results: Of 26, 299 RN patients, 461 (2%) patients underwent IVC-T. Of those, 252 (55%) were non-metastatic vs 209 (45%) were metastatic. Rates of acute kidney injury (AKI), transfusion, cardiac, thromboembolic and other medical complications in non-metastatic vs metastatic patients were 40 vs 40%, 25 vs 22%, 21 vs 23%, 19 vs 14% and 38 vs 40%, respectively (all p ≥ 0.2). Metastatic stage in IVC-T patients did not predict differences in complications in log-link linear GEE regression models (all p > 0.1). However, in logistic regression models with propensity score matching, relying on the overall cohort of RN patients, IVC-T status was associated with higher complication rates (all p < 0.001): AKI (Odds ratio [OR]:2.60; 95%-CI [95%-Confidence interval: 1.97–3.44), transfusions (OR:2.40; 95%-CI: 1.72–3.36), cardiac (OR:2.27; 95%-CI: 1.49–3.47), thromboembolic (OR:9.07; 95%-CI: 5.21–16.58) and other medical complications (OR:2.01; 95%-CI: 1.52–2.66). Conclusions: The current analyses indicate that presence of concomitant IVC-T is associated with higher complication rate at RN. Conversely, metastatic stage has no effect on recorded complication rates. Highlights: RCC patients undergoing radical nephrectomy with concomitant inferior vena cava thrombectomy represent a minority (2% of all RN) within the NIS. Metastatic disease was not associated with higher complications in RN patients with concomitant inferior vena cava thrombectomy. Radical nephrectomy with concomitant inferior vena cava thrombectomy patients should be counseled and treated in a multidisciplinary approach.